2010
DOI: 10.1111/j.1365-2605.2010.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Early activation of sperm by HCO3− is regulated hormonally in the murine uterus

Abstract: Sperm deposited in the female genital tract receive signals for capacitation. Past work indicates that HCO(3) (-) is the initiating signal that the female reproductive tract contains the HCO(3) (-) -permeant anion channel cystic fibrosis transmembrane conductance regulator (CFTR) and that mutations in CFTR cause subfertility in both sexes. In this study, we examined whether CFTR controls uterine HCO(3) (-) content and sperm responses to it. Both CFTR protein and mRNA were absent in prepubertal murine uterus, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…These findings suggest that SLC26A3 and CFTR are part of a complex where, as previously reported [17,18,52], each transporter activity affects the other. Interestingly, inhibition of CFTR [8,41] and SLC26 (this work, data not shown) do not affect tyrosine phosphorylation. This result was not unexpected, since it is likely that capacitation-associated events are not necessarily correlated or connected.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…These findings suggest that SLC26A3 and CFTR are part of a complex where, as previously reported [17,18,52], each transporter activity affects the other. Interestingly, inhibition of CFTR [8,41] and SLC26 (this work, data not shown) do not affect tyrosine phosphorylation. This result was not unexpected, since it is likely that capacitation-associated events are not necessarily correlated or connected.…”
Section: Discussionmentioning
confidence: 64%
“…Experiments using specific CFTR inhibitors strongly suggest that this channel participates in the capacitation-associated hyperpolarization and the AR [9,10], although its inhibition does not affect tyrosine phosphorylation [8,41]. In many cell types, there are interrelationships between the transport of Cl À and HCO 3 À [7, 8,42].…”
Section: Discussionmentioning
confidence: 99%
“…This transport may occur when sperm are exposed to higher HCO 3 -concentrations in the seminal plasma at the time of ejaculation or while migrating to the site of fertilization in the female reproductive tract. In this regard, it was reported that uterine secretions of oestrous female mice contained higher HCO 3 -concentration compared to those in dioestrous (47). This increase correlates with CFTR expression indicating that this channel is upregulated hormonally (47).…”
Section: Discussionmentioning
confidence: 91%
“…In this regard, it was reported that uterine secretions of oestrous female mice contained higher HCO 3 -concentration compared to those in dioestrous (47). This increase correlates with CFTR expression indicating that this channel is upregulated hormonally (47).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation